Influence of the Na+, K+-ATPase inhibitor ouabain on the response of tumour cells to irradiation - Verheye-Dua, Frieda A. A (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Phil.) -- University of Stellenbosch, 1996.